2020
DOI: 10.1101/2020.02.13.947697
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Branched-chain amino acid catabolism depends on GRXS15 through mitochondrial lipoyl cofactor homeostasis

Abstract: Iron-sulfur (Fe-S) clusters are ubiquitous cofactors in all life and are used in a wide array of diverse biological processes, including electron transfer chains and several metabolic pathways. Biosynthesis machineries for Fe-S clusters exist in plastids, the cytosol and mitochondria. A single monothiol glutaredoxin (GRX) has been shown to be involved in Fe-S cluster assembly in mitochondria of yeast and mammals. In plants, the role of the mitochondrial homologue GRXS15 has only partially been characterized. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 87 publications
0
1
0
Order By: Relevance
“…Recently, Cao et al (2019) also revealed that BCAA overaccumulation leads to up-regulation of the target of rapamycin activity, which causes reorganization of the actin cytoskeleton and actin-associated endomembranes in Arabidopsis mutants. In addition, isoleucine was found to serve as a precursor for the synthesis of b-alanine in plants (Rouhier et al, 2019), while in Arabidopsis, a metabolic relationship was revealed between BCAA catabolism and iron-sulfur clusters via the mitochondrial homologue GRXS15 (Moseler et al, 2020).…”
Section: Connections Between Other Amino Acids and Their Related Metabolic Pathwaysmentioning
confidence: 99%
“…Recently, Cao et al (2019) also revealed that BCAA overaccumulation leads to up-regulation of the target of rapamycin activity, which causes reorganization of the actin cytoskeleton and actin-associated endomembranes in Arabidopsis mutants. In addition, isoleucine was found to serve as a precursor for the synthesis of b-alanine in plants (Rouhier et al, 2019), while in Arabidopsis, a metabolic relationship was revealed between BCAA catabolism and iron-sulfur clusters via the mitochondrial homologue GRXS15 (Moseler et al, 2020).…”
Section: Connections Between Other Amino Acids and Their Related Metabolic Pathwaysmentioning
confidence: 99%